Por qué la vulnerabilidad importa. La relación entre masculinidad, emociones y vulnerabilidad en el ejercicio de violencia contra las mujeres en la pareja - de Stéfano Barbero, Matías (2023)
Based on qualitative research that includes participant observation in psycho-socio-educational groups and in-depth interviews with men who exercised intimate partner violence, this article analyzes the relationship between masculinity, emotions, vulnerability and violence. It is suggested that male violence is not only linked to power, but also emerges as a resistance to vulnerability ―as openness to the other, to emotion and the uncertain― that affective bonds demand. The vulnerable position is, at the same time, a position that finds resistance in the mandates of masculinity, but also a necessary position to be able to build conflicts without reaching violence. Psycho-socioeducational groups shows the importance of repoliticizing emotions and vulnerability for social change, especially transforming how masculinity links to violence.